A general approach for the synthesis of bimetallic M–Sn (M = Ru, Rh and Ir) catalysts for efficient hydrogenolysis of ester. Issue 3 (8th December 2016) - Samal, Akshaya K.; Zhu, Haibo; Harb, Moussab; Sangaru, Shiv Shankar; Anjum, Dalaver H.; Hedhili, Mohamed N.; Saih, Youssef; Basset, Jean-Marie
Abstract : A versatile synthetic method was applied for the preparation of Sn containing bimetallic catalysts. Abstract : A versatile synthetic method was applied for the preparation of Sn containing bimetallic catalysts. The synthesis was performed by simply mixing the super hydride [LiB(C2 H5 )3 H], with a metal (Ru, Rh or Ir) salt and an organotin complex in tetrahydrofuran solvent without using any surfactant. This leads to the formation of monodispersed M–Sn (M = Ru, Rh or Ir) bimetallic nanoparticles (NPs). These bimetallic catalysts show high performances in the hydrogenolysis of ester to the corresponding alcohol.